PERAN GREENPEACE DALAM MENANGANI KERUSAKAN LINGKUNGAN AKIBAT PAPARAN MERKURI DI KODAIKANAL INDIA TAHUN 2014 - Sari, Meivi Defita; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research aims to explain the role of Greenpeace International in handling cases of mercury exposure that occurred in Kodaikanal, India. Mercury poisoning at Kodaikanal is a case of mercury contamination that occurred at the Kodaikanal hill station carried out by Hindustan Unilever in the process of making a mercury thermometer for export worldwide.Research data obtained from books, journals, official documents, theses and websites. The researcher uses the perspective of pluralism and analyzes the role of international organizations. The research method used is qualitative data obtained from the literature relating to the research topic.The results of this study indicate that Greenpeace International has an important role in handling this case of mercury exposure. First, Greenpeace International forced Unilever to temporarily suspend the factory operations after working with the Tamil Nadu Pollution Control Board (TNPCB). Second, Greenpeace International helps provide facilities during the process of investigating and cleaning up waste at Kodaikanal. Third, Greenpeace International requests that the Indian government sue Unilever for its negligence and force Unilever to clean up mercury waste at Kodaikanal. Keywords: Mercury, Kodaikanal, Greenpeace International